Pengaruh Return On Asset (ROA), Kompensasi Rugi Fiskal, dan Capital Intensity terhadap Tax Avoidance : Studi Pada Perusahaan Property & Real Estate Yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2021-2023 - Shilvia Yunitasari; Judi Budiman (AKUNTANSI 45, 2025)
This study aims to test the effect of ROA, Fiscal Loss Compensation, and Capital Intensity on Tax Avoidance. The population used in this study is Property & Real Estate Companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. By using the purposive sampling technique, 97 were obtained. The data analysis technique used was the Statistical Package for the Social Sciences (SPSS) version 26. The results of this study indicate that ROA and Fiscal Loss Compensation have a significant effect on Tax Avoidance, while Capital Intensity does not have a significant effect on Tax Avoidance. For further researchers, it is hoped that they can use or add other variables such as company size, leverage, and audit quality.